Iowa RBA, April 22, 1996 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for April 22, 1996. Highlights of the update include sightings of Little Gull, Red-throated Loon, Snowy Egret, Marbled Godwit and a Fish Crow. Also included are handwritten notes for the next week's update with sightings of Willets, Dunlins and Wilson's Phalaropes. Epson - sheet feed/flatbed